The Axenic and Gnotobiotic Mosquito: Emerging Models for Microbiome Host Interactions - Steven, Blaire; Hyde, Josephine; LaReau, Jacquelyn C.; Brackney, Doug E. (Frontiers in Microbiology, 2021)
The increasing availability of modern research tools has enabled a revolution in studies of non-model organisms. Yet, one aspect that remains difficult or impossible to control in many model and most non-model organisms, is the presence and composition of the host associated microbiota, or the microbiome. In this review, we explore the development of axenic (microbe-free) mosquito models and what these systems reveal about the role of the microbiome in mosquito biology. Additionally, the axenic host is a blank template on which a microbiome of known composition can be introduced, also known as a gnotobiotic organism. Finally, we identify a “most wanted” list of common mosquito microbiome members that show the greatest potential to influence host phenotypes. We propose that these are high value targets to be employed in future gnotobiotic studies. The use of axenic and gnotobiotic organisms will transition the microbiome into another experimental variable that can be manipulated and controlled. Through these efforts the mosquito will be a true model for examining host microbiome interactions.